Effect of the temperature on the growth of enterococcus faecalis cultivated in alkaliphilic conditions using hydrolysed sago starch - Seni, anak Empangau (Universiti Malaysia Sarawak (UNIMAS), 2013)
The objective of this study was to investigate the effect of the temperature on the growth of Enterococcus faecalis cultivated in alkaliphilic condition using hydrolysed sago starch. Batch fermentation was carried out in three different temperatures 37 DC, 42 DC and 47°C with pH 8 in 1 L fennentor under an agitation rate 200rpm and supplied by lOOg/L of hydrolysed sago starch. The result showed that, Efaecalis can grow in the three different temperatures with the production of different amount of lactic acid it is was 114.77g/L at temperature 37°C, follow by 42DC it is 102.58g/L and 47 DC is 65. 76g/L. The best temperature for the growth and production of lactic acid in this study is 37 DC.